Appropriation in the commons: variations in the opportunity costs of conservation - Esther Blanco; Maria Claudia Lopez; James M. Walker (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2012)
This study examines individual and group behavior in a linear appropriation game setting. Subjects make decisions from a menu of eight games, without feedback. Four treatment conditions vary the magnitude of the opportunity cost of conservation, including symmetric and asymmetric treatments. A parallel set of four treatments implement the same parameter variations in a setting where probabilistic degradation of the commons is linked to group appropriation. Thus, this setting introduces uncertainty in the value of the opportunity cost of appropriation. In summary, subjects respond systematically to changes in the marginal incentives and to the possibility of degradation. These responses are shown to be related to a direct effect of changes in marginal monetary incentives and to an indirect effect associated with changes in subjects' first order beliefs of the appropriation decisions of others.
Keywords: D7; D3; H4; C90; 330; common-pool resources; asymmetry; cooperation; laboratory experiments